Preliminary evaluation of a non-invasive device for monitoring intracranial pressure waveforms in dogs - Bahr Arias, M. V.; Conceição, R. T.; Guimarães, F. C. [UNESP]; Cardoso, G. S.; Rocha, N. L.F.C. (Wiley, 2022)
Objectives: The objective of this study was to compare waveforms obtained with a new device for the non-invasive monitoring of intracranial pressure (ICP) in dogs with and without neurological disease. Materials and Methods: This prospective study was conducted on both neurologically normal dogs and dogs with neurological diseases. First, non-invasive ICP waveforms were recorded in normal dogs using the Braincare® BcMM 2000 monitor while the dogs were under general anaesthesia induced for procedures unrelated to this study. The dogs were positioned in lateral recumbency, and the sensor was placed over the skin of the parietal region. Secondly, non-invasive ICP waveforms were monitored in dogs with brain and spinal disease until waveforms with characteristic peaks were acquired. All the recorded signals were amplified, filtered and digitalized, by the device, and then transferred to a computer for analysis. Results: Normal pulse waveforms indicating normal brain complacency were observed in eight neurologically normal dogs. In six dogs with brain disease, abnormal pulse waveforms were observed suggesting increased ICP and decreased brain complacency. Four dogs with spinal disease undergoing myelography, had normal waveforms before contrast medium injection and abnormal pulse waveforms during contrast medium injection, indicating a potential increase in ICP. Clinical Significance: Based on these preliminary observations, this method was capable of detecting abnormal pulse waveforms that suggested increased ICP.